2016
DOI: 10.1177/00333549161310s206
|View full text |Cite
|
Sign up to set email alerts
|

“Know Hepatitis B:” A Multilingual Communications Campaign Promoting Testing for Hepatitis B Among Asian Americans and Pacific Islanders

Abstract: The "Know Hepatitis B" campaign was the first national, multilingual communications campaign to promote testing for hepatitis B virus (HBV) among Asian Americans and Pacific Islanders (AAPIs). This population comprises fewer than 5% of the total U.S. population but accounts for more than half of the up to 1.4 million Americans living with chronic HBV infection. To address this health disparity with a national campaign, CDC partnered with Hep B United, a national coalition of community-based partners working to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Other recommended interventions to promote uptake of hepatitis testing and linkage to care include peer and lay health worker support in community-based settings, clinician reminders to offer testing, and testing as part of integrated services, alongside the use of different media strategies to promote awareness about hepatitis in the general population [ 6 , 15 , 59 , 60 ].…”
Section: Technological Advances and Innovations To Improve Access To mentioning
confidence: 99%
“…Other recommended interventions to promote uptake of hepatitis testing and linkage to care include peer and lay health worker support in community-based settings, clinician reminders to offer testing, and testing as part of integrated services, alongside the use of different media strategies to promote awareness about hepatitis in the general population [ 6 , 15 , 59 , 60 ].…”
Section: Technological Advances and Innovations To Improve Access To mentioning
confidence: 99%
“…The majority of people with CHB live in countries that now have national viral hepatitis plans [11]. Many of these plans encompass population-specific communications campaigns to improve awareness and promote testing [12]; community-based programs to provide testing and linkage to care to under-served and high-risk communities [13][14][15]; and pilot projects integrating HBV testing and care into health systems to improve the capacity of primary care providers to test and manage people with CHB [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several strategies identified that lead to increased testing and linkage to care for persons with HBV that may be applied to address gaps for pregnant women with HBV infection identified in this study. Patient education has shown success by facilitating increased HBV testing in hard to reach populations [ 15 , 17 , 18 ] and can be applied to pregnant women. In addition, provider education is important to ensure HBV testing is performed and correctly interpreted, and persons with positive results receive appropriate management [ 19 ], which can be applied to prenatal care clinics.…”
Section: Discussionmentioning
confidence: 99%